Risk of Bleeding with Exposure to Warfarin and Nonsteroidal Anti-Inflammatory Drugs: A Systematic Review and Meta-Analysis - Villa Zapata, Lorenzo; Hansten, Philip D.; Panic, Jennifer; Horn, John R.; Boyce, Richard D.; Gephart, Sheila; Subbian, Vignesh; Romero, Andrew; Malone, Daniel C. (Thrombosis and Haemostasis, 2020)
Background Warfarin use can trigger the occurrence of bleeding independently or as a result of a drug–drug interaction when used in combination with nonsteroidal anti-inflammatory drugs (NSAIDs).Objectives This article examines the risk of bleeding in individuals exposed to concomitant warfarin and NSAID compared with those taking warfarin alone (Prospero Registry ID 145237).Methods PubMed, EMBASE, Scopus, and Web of Science were searched. The primary outcome of interest was gastrointestinal bleeding and general bleeding. Summary effects were calculated to estimate average treatment effect using random effects models. Heterogeneity was assessed using Cochran's Q and I2. Risk of bias was also assessed using the Agency for Healthcare Research and Quality bias assessment tool.Results A total of 651 studies were identified, of which 11 studies met inclusion criteria for meta-analysis. The odds ratio (OR) for gastrointestinal bleeding when exposed to warfarin and an NSAID was 1.98 (95% confidence interval [CI]: 1.55–2.53). The risk of gastrointestinal bleeding was also significantly elevated with exposure to a COX-2 inhibitor and warfarin relative to warfarin alone (OR = 1.90, 95% CI: 1.46–2.46). There was an increased risk of general bleeding with the combination of warfarin with NSAIDs (OR = 1.58, 95% CI: 1.18–2.12) or COX-2 inhibitors (OR = 1.54, 95% CI: 0.86–2.78) compared with warfarin alone.Conclusion Risk of bleeding is significantly increased among persons taking warfarin and a NSAID or COX-2 inhibitor together as compared with taking warfarin alone. It is important to caution patients about taking these medications in combination.
Keywords: warfarin; nonsteroidal anti-inflammatory drug; cyclooxygenase-2 inhibitors; gastrointestinal hemorrhage; drug interactions